Ackee (Blighia sapida) fruit arils: Nutritional, phytochemicals and antioxidant properties - Dossou, Veronica M.; Agbenorhevi, Jacob K.; Combey, Sussana; Afi-Koryoe, Sarah (International Journal of Nutrition and Food Sciences, 2024)
This is an article published by Veronica M. Dossou, Jacob K. Agbenorhevi, Sussana Combey, Sarah Afi-Koryoe. Ackee (Blighia sapida) Fruit Arils: Nutritional, Phytochemicals and Antioxidant Properties. International Journal of Nutrition and Food Sciences. Vol. 3, No. 6, 2014, pp. 534-537. doi: 10.11648/j.ijnfs.20140306.17